Rural-to-urban migration in Vietnam: Trend and institutions - Nguyen Anh, Dang (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
: Vietnam’s high economic growth and rapid urbanization has increased the number of people moving within the country, largely from rural areas to major cities in search of economic opportunities and a better life. The country’s constitutional framework provides people with a basic freedom to relocate internally and to earn a living of their choice. However the current migration institutions (such as the Ho Khau registration system) give limited access to public services to those without permanent household registration. The system continues to increase the costs of migration and deepens social inequalities. The present paper examines the key patterns of rural-to-urban migration, and provides a better understanding of the system of Ho Khau and its consequences for migrants in their places of destination. The paper suggests basic measures that aim at reducing, relaxing and restructuring the institutional constraints on migration. Such reforms are essential to enhance the economic efficiency of major cities and treat migration as a positive factor for social inclusion and national development. Received 10th April 2017; Revised 27th April 2017; Accepted 31st April 2017